Perilobar Nephroblastomatosis: Natural History and Management - S. Stabouli; N. Printza; J. Dotis; A. Matis; D. Koliouskas; N. Gombakis; F. Papachristou (Hindawi Limited, 2014)
Nephroblastomatosis (NB) has been considered as a precursor of Wilms tumor (WT). The natural history of NB seems to present significant variation as some lesions may regress spontaneously, while others may grow and expand or relapse and develop into WT later in childhood. Although, most investigators suggest adjutant chemotherapy, the effect and duration of treatment are not well established. Children with diffuse perilobar NB, Beckwith-Wiedemann syndrome, and hemihypertrophy seem to particularly benefit from treatment. We discuss our experience on two cases of NB and we review the literature for the management of this rare condition.